RANCANG BANGUN PLTS SEBAGAI SUPLAI TENAGA SMART CONTROL SYSTEM ELEKTROLISIS AIR HUJAN DI SMAN 1 MENGWI - Danu Tri Damarta, Nyoman; Raka Agung, I Gusti Agung Putu; Budiastra, I Nyoman; Divayana, Yoga (Jurnal SPEKTRUM, 2025)
The use of Solar Power Plants (PLTS) as a renewable energy source is a solution to support energy efficiency and sustainability. This study aims to design and evaluate a PLTS system as the power source for a Smart Control System in the rainwater electrolysis system at SMAN 1 Mengwi. The evaluation includes Peak Sun Hours (PSH) to assess solar energy absorption efficiency and battery capacity to ensure system continuity. The results indicate that the PSH values align with Global Solar Atlas data, with a Mean Absolute Percentage Error (MAPE) of 6.163%, categorized as Very Good. Additionally, the system can supply 27.265 Wh per day, allowing 10 days of operation without recharging. These findings confirm that the PLTS system is a reliable energy source for the Smart Control System, supporting energy efficiency while reducing reliance on conventional electricity. The implementation of this system is expected to promote green energy adoption in schools and contribute to broader renewable energy utilization.